Building organisational citizenship behaviour with local wisdom: an analysis of religiosity, mutual aid, transformational leadership, and work motivation mediation - Desi Puspitosari; Sri Setyaningsih; Lina Novita (Jurnal Konseling dan Pendidikan, 2025)
This study examines the influence of local wisdom and organizational factors on teacher Organizational Citizenship Behavior (OCB) in state Islamic junior high schools (MTs Negeri) in Jakarta, Indonesia. Using a sequential exploratory mixed-methods design (POP-SDM), the research identifies religiosity, mutual assistance, and transformational leadership as exogenous variables, with work motivation as an intervening variable. Quantitative data from 220 teachers were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings confirm that transformational leadership has the strongest direct effect on OCB (β = 0.397), followed by work motivation (β = 0.221), religiosity (β = 0.197), and mutual assistance (β = 0.215). Work motivation significantly mediates the relationships between religiosity and OCB, and between mutual assistance and OCB, but not between transformational leadership and OCB. The study demonstrates the critical role of work motivation as a psychological bridge, transforming intrinsic values of religiosity and a collaborative spirit into tangible extra-role behaviors. This research enriches OCB theory by integrating cultural dimensions and offers practical strategies for enhancing teacher performance through culturally informed human resource development.